CLINICAL CARE PATHWAY AND MANAGEMENT OF MAJOR BLEEDING ASSOCIATED WITH NON-VITAMIN K ANTAGONIST ORAL ANTICOAGULANTS: A MODIFIED DELPHI CONSENSUS FROM SAUDI ARABIA AND UAE - Abdulrahman Al Raizah; Fakhr Alayoubi; Galal Hassan Abdelnaby; Hazzaa Alzahrani; Majid Farraj Bakheet; Mohammed A Alskaini; Rasha Buhumaid; Sameer Al Awadhi; Sara Nooruddin Kazim; Thiagarajan Jaiganesh; Zohair Al Asiri (Mediterranean Journal of Hematology and Infectious Diseases)
Background: The non-vitamin K antagonist oral anticoagulants (NOACs) have become the mainstay anticoagulation therapy for patients requiring oral anticoagulants (OACs) in the Gulf Council Cooperation (GCC) countries. The frequency of NOAC-associated major bleeding is expected to increase in the Emergency Department (ED). Nonetheless, we still lack local guidelines and recommendations for bleeding management in the region. The present Delphi-based consensus aims to establish a standardized and evidence-based clinical care pathway for managing NOAC-associated major bleeding in the Kingdom of Saudi Arabia (KSA) and the United Arab Emirates (UAE).